Determination of the soil moisture recession constant from satellite data: a case study of the Yucatan peninsula. Issue 20 (18th October 2017) - Romero, David; Torres-Irineo, Edgar; Kern, Stefan; Orellana, Roger; Hernandez-Cerda, Maria Engracia
ABSTRACT: Estimation of the recession constant for soil moisture can assist in soil and water management. This article estimates soil moisture recession velocity from satellite data, thereby taking advantage of extensive data coverage in a metric that is more commonly used with point data for rivers. Retrieval from satellites of the surface soil moisture has produced global coverage of multiannual time series data, thereby allowing the application of techniques that require long time series of daily data. We applied two techniques from river hydrology to soil moisture data from the advanced scatterometer aboard the meteorological operational satellite: (1) baseflow separation; and (2) master recession curve (MRC) with the correlation method. The former filtered the data and extracted those for the base soil moisture (BSM), which is considered the water that circulates in the soil by capillarity. The latter technique allowed the estimation of recession constants by the extraction of continuously decreasing BSM segments. The use of MRC for a large range of BSM provides a recession constant representative of all the moisture decrease for each pixel, thereby permitting the identification of drought-sensitive zones. The recession constant, a metric that had not been used for soil moisture, allowed us to determine potential temporal evolution of drought in the Yucatan peninsula. Government agencies could use the approach applied in this study to improve water management and drought prevention.